A discrete-time queueing system with changes in the vacation times - Atencia, Ivan (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers a discrete-time queueing system in which an arriving customer can decide to follow a last come first served (LCFS) service discipline or to become a negative customer that eliminates the one at service, if any. After service completion, the server can opt for a vacation time or it can remain on duty. Changes in the vacation times as well as their associated distribution are thoroughly studied.
Keywords: discrete-time queueing theory; changes in the remaining vacation times; busy period; sojourn times